Life cycle assessment of auto-tropically cultivated economic microalgae for final products such as food, total fatty acids, and bio-oil - Zhang, Dan; An, Siyuan; Yao, Rao; Fu, Wen; Han, Yujie; Du, Ming; Chen, Zixi; Lei, Anping; Wang, Jiangxin (Frontiers in Marine Science, 2022)
Life cycle assessment (LCA) is a powerful tool to evaluate environmentally sustainable production or consumption of various goods or services. Microalgae are single-celled green factories and good resources of biofuels, bioactive products, food ingredients, and degradable biomaterials. Currently, microalgae are also valuable for mitigating elevated greenhouse gases like CO2 levels and treatment of wastewater. LCA evaluation was limited and separated, majorly in microalgal biofuels and heterotrophic cultivation. Comparative LCA for different final algal products such as algal powder, bio-oil, total fatty acid, and residue recycling is still limited, especially autotrophic algal cultivation for products other than bio-oils and biofuels. Thus, we chose several autotrophic cultivated microalgae and made a comparative LCA among these selected species and a detailed step-by-step production in Chlorella sp. Results indicated that we could significantly reduce the production cost and lower environmental impacts by selecting algal species and final products, optimizing methods for algal cultivation, biomass separation, and drying process, and land selection plus electricity renewable energy, together with thermal power plants nearby for CO2 or flu gas. It shed light on the insight of microalgal consumption selection under current international requirements and challenges for carbon sequestration.